IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (ADD) DALAM MENINGKATKAN PEMBANGUNAN DESA (Studi Kasus di Desa Mojoranu Kecamatan Sooko Kabupaten Mojokerto) - Nafi’atin Riski; Abdul Wahid Mahsuni; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe principle of real autonomy is a principle that to deal with governmentalaffairs is carried out based on the tasks, authorities, and obligations that actuallyexist and have the potential to grow and develop in accordance with the potentialand uniqueness of the region. Thus the content and type of autonomy for eachregion is not always the same as other areas. The definition of responsibleautonomy is the autonomy whose implementation must be completely in line withthe objectives and intent of granting autonomy, which is basically to empower theregion including improving the welfare of the people which is a major part of thenational goal. Along with that principle the implementation of regional autonomyshould always be oriented towards improving the welfare of the community byalways paying attention to the interests and aspirations that grow in society.Keywords: Village Government, Public Policy Implementation, Village FundAllocation